Molecular Characterization of blaIMP–4-Carrying Enterobacterales in Henan Province of China - Liu, Wentian; Dong, Huiyue; Yan, Tingting; Liu, Xuchun; Cheng, Jing; Liu, Congcong; Zhang, Songxuan; Feng, Xiang; Liu, Luxin; Wang, Zhenya; Qin, Shangshang (Frontiers in Microbiology, 2021)
Carbapenem-resistant Enterobacterales (CRE) pose a serious threat to clinical management and public health. We investigated the molecular characteristics of 12 IMP-4 metallo-β-lactamase producing strains including 5 Enterobacter cloacae, 3 Escherichia coli, 2 Klebsiella pneumoniae and 2 Citrobacter freundii. These strains were collected from a tertiary teaching hospital in Zhengzhou from 2013 to 2015. The minimum inhibitory concentrations (MICs) results showed that each blaIMP-4-positive isolate was multidrug-resistant (MDR) but susceptible to colistin. All of the E. coli belonged to ST167, two C. freundii isolates belonged to ST396, and diverse ST types were identified in E. cloacae and K. pneumoniae. S1-PFGE, southern blotting and PCR-based replicon typing assays showed that the blaIMP-4-carrying plasmids ranged from ~52 to ~360 kb and belonged to FII, FIB, HI2/HI2A and N types. N plasmids were the predominant type (8/12, 66.7%). Plasmid stability testing indicated that the blaIMP-4-carrying N type plasmid is more stable than the other types of plasmids. Conjugative assays revealed that three of the blaIMP-4-carrying N plasmids were transferrable. Complete sequence analysis of a representative N type (pIMP-ECL14-57) revealed that it was nearly identical to pIMP-FJ1503 (KU051710) (99% nucleotide identity and query coverage), an N type blaIMP-4-carrying epidemic plasmid in a C. freundii strain. PCR mapping indicated that a transposon-like structure [IS6100-mobC-intron (K1.pn.I3)-blaIMP-4-IntI1-IS26] was highly conserved in all of the N plasmids. IS26 involved recombination events that resulted in variable structures of this transposon-like module in FII and FIB plasmids. The blaIMP-4 gene was captured by a sul1-type integron In1589 on HI2/HI2A plasmid pIMP-ECL-13-46.